Regioselective synthesis of spiro naphthofuranone-pyrazoline via a [3+2] cycloaddition of benzoaurones with nitrile imines. Issue 31 (31st July 2020) - Su, Yingpeng; Ma, Chenglong; Zhao, Yanan; Yang, Caixia; Feng, Yawei; Wang, Ke-Hu; Huang, Danfeng; Huo, Congde; Hu, Yulai
Graphical abstract: Image 1 Highlights: A regioselective [3 + 2] cycloaddition reaction of benzoaurones with nitrile imines was developed. A series of compelling spiro [naphthofuran-2, 3′-pyrazoline]-3-ones were efficiently obtained. The reaction displayed good gram-scale capacity.